Perlindungan Konsumen Terhadap Peredaran Produk Kosmetik Mengandung Bahan Berbahaya yang Merugikan Konsumen (Studi Analisis Produk Kosmetik Temulawak New Day & Night Cream Beauty Whitening) - Putri, Ela Oktavia; Reykasari, Yunita (Indonesian Journal Publisher, 2023)
The definition of cosmetics according to Article 1 number (1) of the Republic of Indonesia Minister of Health Regulation Number 176/MenKes/PER/VIII/2010 concerning Determination of the term Cosmetics is a material or preparation whose use is application outside the human body to change the appearance or improve and maintain the body. Women are required to have types of cosmetics such as powder, eyebrow pencil and lipstick. Apart from domestic cosmetic products, cosmetics markets from abroad can also enter Indonesia because of rapid globalization. Cosmetic products created as a result of the development of the pharmaceutical industry further bind women's desire to look beautiful and perfect, therefore all situations are exploited by a group of irresponsible entrepreneurs who produce or sell cosmetics that do not meet the requirements. The government promulgated Law Number 8 of 1999 concerning Consumer Protection to ensure that consumers are fully protected and provide requirements for cosmetic products. Even though the above regulations have been confirmed and promulgated, there is still disobedience by business actors in trading activities regarding the cosmetics they produce containing dangerous ingredients. An example is the distribution of the Temulawak New Day & Night Cream Beauty Whitening cosmetic product which contains mercury. This also includes violating Article 4 letter c of the Consumer Protection Law (UUPK), cosmetic products that are bought and sold containing mercury-containing ingredients are an example of a lack of supervision by the government and the Food and Drug Supervisory Agency (BPOM) so that the products These cosmetic products can still circulate in the community. One product that is currently popular and in demand by many people is the Temulawak New Day & Night Cream Beauty Whitening cosmetic, which is known to be distributed throughout the Republic of Indonesia and is known to contain dangerous substances, namely mercury.